Gas accretion onto the disc of a simulated Milky Way-mass galaxy - Iza, F. G. (2021)
In the standard paradigm of galaxy formation and evolution, the baryonic component of galaxies forms from the collapse and condensation of gas within dark matter haloes, and later grows from continuous accretion of gaseous mass, both in diffuse form and in mergers with other systems. After a first period of rapid and violent halo growth, the gas settles into a rotationally-supported structure, eventually giving rise to the formation of a stellar disc. Stars evolve and return chemically-processed gas and energy to the interstellar medium, mainly through Type II supernova explosions. In the disc region, the cosmological accretion of gas combines with the outflows resulting from supernovae, affecting the hydrodynamical and structural properties of the disc and producing gas flows in the vertical and radial directions. In this work, we use a simulation of the Auriga Project, a suite of magneto-hydrodynamical, zoom-in cosmological simulations of Milky Way-like galaxies, to study the temporal and radial dependencies of gas accretion onto the disc. We also investigate the disc evolution, focusing on the inside-out disc formation scenario, which is one of the fundamental hypotheses of chemical evolution models of the Galaxy.